Spatial analysis of access to and accessibility to surrounding train stations: a case study of accessibility for the elderly in Perth, Western Australia - Lin, Ting (Grace); Xia, Jianhong (Cecilia); Robinson, Todd; Goulias, K.; Church, R.; Olaru, D.; Tapin, J.; Han, R. (Elsevier, 2014)
Approximately one-fifth of Perth’s population is aged 60 or older. Projections suggest that this proportion will continue to increase as a result of the large number of children born after the World War II (1946–1964). Access to and accessibility around train stations for the aging population is and will become a more important issue as the elderly population continues to grow. The aim of the paper is to develop and apply anew measure of accessibility to train stations at a fine spatial scale, justified by the special circumstance of the elderly using a case study in Perth, Western Australia. Intercept surveys are used to collect data on factors affecting train station accessibility for patrons aged 60 years or older, at seven highly dispersed train stations. Overall accessibility is measured separately using a composite index based on three travel modes (walk-and-ride, park-and-ride and bus-and-ride). The results illustrate that key variables, such as distance from an origin to a station, walking or driving route directness, land-use diversity, service and facility quality, bus connection to train stations, all affect the accessibility to train stations for the elderly. This implies that improvements to these factors will improve accessibility for this population group.